A role for β‐catenin in diet‐induced skeletal muscle insulin resistance. Issue 4 (17th February 2023) - Masson, Stewart W. C.; Dissanayake, Waruni C.; Broome, Sophie C.; Hedges, Christopher P.; Peeters, Wouter M.; Gram, Martin; Rowlands, David S.; Shepherd, Peter R.; Merry, Troy L.
Abstract: A central characteristic of insulin resistance is the impaired ability for insulin to stimulate glucose uptake into skeletal muscle. While insulin resistance can occur distal to the canonical insulin receptor‐PI3k‐Akt signaling pathway, the signaling intermediates involved in the dysfunction are yet to be fully elucidated. β‐catenin is an emerging distal regulator of skeletal muscle and adipocyte insulin‐stimulated GLUT4 trafficking. Here, we investigate its role in skeletal muscle insulin resistance. Short‐term (5‐week) high‐fat diet (HFD) decreased skeletal muscle β‐catenin protein expression 27% ( p  = 0.03), and perturbed insulin‐stimulated β‐catenin S552 phosphorylation 21% ( p  = 0.009) without affecting insulin‐stimulated Akt phosphorylation relative to chow‐fed controls. Under chow conditions, mice with muscle‐specific β‐catenin deletion had impaired insulin responsiveness, whereas under HFD, both mice exhibited similar levels of insulin resistance (interaction effect of genotype × diet p  < 0.05). Treatment of L6‐GLUT4‐myc myocytes with palmitate lower β‐catenin protein expression by 75% ( p  = 0.02), and attenuated insulin‐stimulated β‐catenin phosphorylation S552 and actin remodeling (interaction effect of insulin × palmitate p  < 0.05). Finally, β‐catenin S552 phosphorylation was 45% lower in muscle biopsies from men with type 2 diabetes while total β‐catenin expression was unchanged. These findings suggest that β‐catenin dysfunction is associated with the development of insulin resistance. Abstract : β‐catenin is an emerging regulator of insulin‐stimulated glucose transport. Here, we demonstrate lower β‐catenin protein abundance in insulin resistant mice, and perturbed β‐catenin phosphorylation in men with type 2 diabetes.